المهارات التّعبيرية وتحقيق الذّات عند متعلمي السّنة الرّابعة من التّعليم المتوسط - دراسة ميدانية لبعض متوسّطات ولاية الوادي - حمدان, الزهرة; بالعيد, هاجر (University of Eloued جامعة الوادي, 2024)
الحمد لله الذي خصنا باللغة العربية أو لغة الضاد لسانا ، فاللغة أدقﹼً أداة يمتلكها المتعلم للتعبير عن أفكاره ومشاعره وواقعه ، وللتواصل اللغوي يستعمل المتعلم فنا من المهارات اللغوية الأربعة التي نحن بصدد ضبط مفاهيمها وإبراز دورها في تحقيق الذات لدى المتعلم في بحثنا الموسوم بــ : المهارات التعبيرية وتحقيق الذات عند متعلمي السنة الرابعة من التعليم المتوسط ـ دراسة ميدانية لبعض متوسطات ولاية الوادي ـ وبعد الدراسة النظرية والميدانية لهذا الموضوع حاولنا الإجابة عن بعض الإشكاليات تمحور أهمها فيما يلي: ـ ما مفهوم المهارات اللغوية وما دورها في التواصل اللغوي؟ ـ ما مدى اكتساب متعلم السنة الرابعة من التعليم المتوسط للمهارات اللغوية والتعبيرية؟ ـ ما مدى إسهام المهارات اللغوية في تنمية المهارات التعبيرية وتحقيق الذات عند متعلمي الرابعة متوسط ؟ وقد وقع اختيارنا لهذا الموضوع لأسباب ذاتية ارتبطت بطبيعة عملنا فبعد خوضنا لمهنة التعليم استوقفنا نشاط التعبير لما له من أهمية بالغة في تكوين شخصية المتعلم ، وأخرى موضوعية تمثلت في محاولة الكشف عن مدى أهمية المهارات اللغوية والتعبيرية بالنسبة للمتعلم وإبراز دورها في تحقيق ذاته . وللوصول إلى الهدف المنشود من هذا البحث اتبعنا المنهج الوصفي بإجراءات التحليل مع الاستعانة بالمنهج الإحصائي في تحليل البيانات . وللإجابة عن الإشكاليات المطروحة اعتمدنا خطة بحث قسمت إلى فصلين ، حاولنا في الفصل الأول [ ضبط المفاهيم النظرية وذلك بالبحث عن مفهوم المهارات اللغوية وأنواعها ، وكذا المهارات التعبيرية وتحقيق ] . أما الفصل الثاني [ فدارت محطاته حول الكشف عن مستوى الكفاية التعبيرية لمتعلمي الرابعة متوسط ودورها في تحقيق ذاته ، وذلك من خلال وصف إنتاجاتهم التعبيرية الشفوية منها والكتابية وتحليلها ] . من خلال دراستنا للموضوع بشقيه النظري والتطبيقي؛ توصلنا إلى جملة من النتائج، تمثل أهمها في: -انعدام استعمال اللغة العربية في الوسط الذي يحي فيه متعلم السنة الرابعة من التعليم المتوسط إلا ما ندر. - عدم تدرب متعلم السنة الرابعة من التعليم المتوسط على الإنشاء والتحرير في أوقات فراغه. - غياب الأنشطة التثقيفية في الوسط المدرسي. - جمود النصوص وعدم ملامستها لواقع متعلم السنة الرابعة من التعليم المتوسط. - قلة استثمار فن الاستماع للبرامج التثقيفية أو الأخبار التي تنطق بالعربية الفصحى. ومن خلال عملية البحث والتقصي؛ خلصنا إلى مجموعة من المقترحات، التي من شأنها أن تقلل من هذا الضعف، والتي يتمثل أهمها في: - تشجيع الكتاتيب على تحفيظ الأراجيز والأحاديث النبوية، وعدم الاكتفاء بتحفيظ (القرآن الكريم) فقط دون شرح أو تمرن على الكتابة على الألواح، التي تساعد على الحفظ. - توفير حصص ولو سويعة في البرنامج الدراسي، تخصّص للمطالعة. - إعادة النظر في المواضيع المبرمجة في نشاطي التعبير الكتابي والشفوي، وإقحام المعلم في اقتراح مواضيع تتناسب والمستوى الإدراكي المتعلم. Praise be to God who gave us the Arabic language, or the language of Dād, as a language. Language is the most accurate tool that the learner possesses to express his thoughts, feelings, and reality. For linguistic communication, the learner uses one of the four linguistic skills whose concepts we are in the process of controlling and highlighting their role in the learner’s self-realization in our research tagged with: Expressive skills and self-realization among fourth-year middle school learners - A field study of some averages in the state of El Oued After the theoretical and field study of this topic, we tried to answer some of the problems, the most important of which are as follows: What is the concept of linguistic skills and what is their role in linguistic communication? To what extent does the learner of the fourth year of intermediate education acquire linguistic and expressive skills? - To what extent do language skills contribute to the development of expressive skills and self-realization among learners? Fourth average? We chose this topic for subjective reasons linked to the nature of our work. After entering the teaching profession, we stopped the activity of expression because of its great importance in shaping the learner’s personality, and another objective matter represented in an attempt to reveal the importance of linguistic and expressive skills for the learner and highlight their role in self-actualization. To reach the desired goal of this research, we followed the descriptive approach to analysis procedures while using the statistical approach in analyzing the data. In order to answer the problems raised, we adopted a research plan that was divided into two chapters. In the first chapter, we tried [to control theoretical concepts by researching the concept of linguistic skills and their types, as well as expressive skills and achievement]. As for the second chapter, [its stations revolved around revealing the level of expressive competence of fourth-intermediate learners and its role in self-fulfillment, by describing and analyzing their expressive productions, both oral and written]. Through our study of the subject, both theoretical and applied, We reached a number of results, the most important of which are: -The lack of use of the Arabic language in the environment in which the learner lives in the fourth year of intermediate education, except in rare cases. - The fourth year of intermediate education learner is not trained to compose and edit in his spare time. - The absence of educational activities in the school environment. - The stagnation of texts and their lack of touch with the reality of the learner in the fourth year of middle school. - Lack of investment in the art of listening to educational programs or news that are spoken in classical Arabic. Through the process of research and investigation; We concluded a set of proposals that would reduce this weakness, the most important of which are: - Encouraging writers to memorize verses and hadiths of the Prophet, and not to limit themselves to memorizing (the Holy Qur’an) only without explaining or practicing writing on tablets, which helps in memorization. - Providing even short sessions in the academic program, devoted to reading. - Reconsidering the topics programmed in the written and oral expression activities, and involving the teacher in proposing topics that suit the learner’s cognitive level.
لسانيات عامة
Keywords: المهارات التعبيرية، تحقيق الذات، المستوى الإدراكي المتعلم.; : Palestine - Algerian folk poetry of the folk Semantic and aesthetic dimensions